Longitudinal evaluation of the Ophthalmology residents in Brazil: an observational prospective study - Iyeyasu, Josie Naomi; Fernandes, Dario Cecilio; Carvalho, Keila Monteiro de (São Paulo Medical Journal, 2023)
BACKGROUND: The longitudinal evaluation of students seems to be a better way to assess their knowledge compared with that of the traditional methods of evaluation, such as modular and final tests. Currently, progress testing is the most consolidated type of longitudinal testing method. However, despite being well consolidated as an assessment tool in medical education, the use of this type of test in residency programs is scarce. OBJECTIVES: This study aimed to investigate residents’ knowledge growth regarding residency training and to describe the implementation of a longitudinal evaluation test in ophthalmological residency training across several medical schools in Brazil. Finally, the study aimed to check whether performance in the tests can be used as a predictor of the results of the specialist title test. DESIGN AND SETTING: This was a prospective observational study. This study was conducted using an online platform. METHODS: Online tests were developed following the same pattern as the Brazilian Ophthalmology Council specialist tests. All the residents performed the test simultaneously. The tests were conducted once a year at the end of the school year. RESULTS: A progress test was conducted across 13 services with 259 residents. Our results demonstrated that resident scores improved over the years (P < 0.0001) and had a moderate correlation with the Brazilian Opthalmology Council specialist test (P = 0.0156). CONCLUSION: The progress test can be considered a valuable tool to assess knowledge, meaning their knowledge increased over residency training. In addition, it can be used as a predictor of the result in the specialist title test.